Trait correlates of success at work. (March 2017) - Teodorescu, Alexandra; Furnham, Adrian; MacRae, Ian
Abstract: Identifying and developing high potential individuals is fundamental to successful companies and organizations. The present study focuses on the personality traits of high potential individuals. The High Potential Traits Inventory (HPTI) was used to investigate associations between personality traits and measures of career success, in a sample of 383 employed individuals. Results indicate HPTI personality traits relate to subjective and objective measures of success with Conscientiousness being the strongest predictor. The findings of the current study are consistent with previous research on High Flyers. Implications of the current study are discussed, suggesting a clearer operationalization of success is crucial for understanding the underlying mechanisms which lead from personality to potential.